2018
DOI: 10.29173/mocs34
|View full text |Cite
|
Sign up to set email alerts
|

Modular Industry Characteristics and Barriers to its Increased Market Share

Abstract: Modular and offsite construction reduces project duration and cost by synchronizing offsite and onsite work. Project activities are constructed in a controlled offsite facility to minimize effects of inclement weather and site disruptions, while meeting safety and quality requirements. In recent years, many organizations have conducted questionnaires to study characteristics of modular and offsite construction, such as the Modular Building Institute (MBI), Buildoffsite campaigning organisation in the UK, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…All told, these studies did not investigate some of current practices in modular construction such as project financing, standards and regulations, type of project delivery system, type of contracts, type of procurement method, synchronization of onsite and offsite schedules, BIM applications and software, scheduling software, and barriers to increased market share. Thus, this paper studies these practices and presents comprehensive analysis for the conducted questionnaire that was briefly introduced earlier since no thorough analysis was presented earlier for all the studied practices [30][31][32]. This paper also presents current efforts around the world dedicated to overcome the barriers and challenges facing modular and offsite construction and it investigates current practices and industry characteristics of modular construction in the context of the aforementioned gaps in the body of knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…All told, these studies did not investigate some of current practices in modular construction such as project financing, standards and regulations, type of project delivery system, type of contracts, type of procurement method, synchronization of onsite and offsite schedules, BIM applications and software, scheduling software, and barriers to increased market share. Thus, this paper studies these practices and presents comprehensive analysis for the conducted questionnaire that was briefly introduced earlier since no thorough analysis was presented earlier for all the studied practices [30][31][32]. This paper also presents current efforts around the world dedicated to overcome the barriers and challenges facing modular and offsite construction and it investigates current practices and industry characteristics of modular construction in the context of the aforementioned gaps in the body of knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First hypothesis: Negative stigma is a barrier to increased market share As shown in Figure 5, more than half of respondents agreed that there is negative stigma associated with modular construction, which can be attributed to the misconception that modular is intended primarily for temporary, single-storey applications. The percentage of respondents who agreed that the significant advantages of modular construction are not effectively communicated with owners is 70%, while 80% of respondents agreed that there is a lack of well-designed marketing campaigns conducted by modular institutions and manufacturers, and 90% of respondents agreed that owners are not familiar with the various products offered by the modular industry [30]. While 81.5% of respondents agreed that the modular industry lacks large-scale partnerships and corresponding market share due to the focus of modular manufacturers on local markets, there is also consensus that a lack of academic research highlighting the advantages of modular construction is a factor (83.6% of respondents, as shown in Figure 6).…”
Section: Barriers To Increased Market Sharementioning
confidence: 99%
See 2 more Smart Citations
“…Despite all the benefits of 3D scanning and BIM in detecting the discrepancies, still there are other technologies such as Virtual Reality (VR) and Virtual Manipulation (VM) that can help to improve discrepancy detection process. In a survey, the industry professionals indicated that using VR along with BIM is one of the main solutions for the future of their company and the industry (Salama et al 2018). VR can provide a one to one scale level of BIM (Heydarian et al 2015), therefore it is possible to improve discrepancy detection in such environments.…”
Section: Introductionmentioning
confidence: 99%